The Theology of Alexander Knox (1757-1831) - McCready, David John William (Irish School of Ecumenics, 2012)
This thesis describes and analyses the theology of the Irish Anglican layman, Alexander Knox (1757-1831), which is here for the first time explored in depth. The method it uses is historical, focusing on Knox’s published writings and unpublished papers. It examines what these primary sources say, and seeks to understand them in the light of their context, both synchronic and diachronic.
Keywords: Religions, Theology & Ecumenics, Ph.D.; Ph.D. Trinity College Dublin